THEMATIC INVESTIGATIONS WITH INDONESIAN EFL PRE-SERVICE TEACHERS: FROM DESCRIPTIONS TO SOCIAL CRITIQUES AND BEYOND - Joseph Ernest Mambu (Indonesian JELT, 2009)
This paper aims at illuminating EFL educators with the application of “thematic investigation” as endorsed by a Critical Pedagogy exponent, Paulo Freire. The investigation involved 14 EFL pre-service (student) teachers and me as a teacher-researcher. In the investigation, four pictures (a McDonald’s advertisement, a beauty pageant, a crowded city, and a beggar in front of a temple) became the media for these teachers to make sense of realities. Using English as the medium of expression, these teachers suggested nuanced interpretations of the pictures. In view of various senses of “critical”, the student teachers’ interpretations represented various “breadths” and “depths” (i.e., the scope) of criticality. Knowing the scope of criticality is essential in being more aware of limits that restrict one’s views. The analyses on the generated themes will become the bases for further reflections to transcend the restrictions of one’s own perspectives. Keywords: Critical thinking; social critiques; thematic “limit-situation(s)”; problematizing practices.